1999
DOI: 10.1292/jvms.61.749
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemic of Parapoxvirus Infection among Cattle: Isolation and Antibody Survey.

Abstract: ABSTRACT. A disease characterized by papules, nodules, vesicles and, rarely, pustules and ulcers on teats was seen among cattle on a farm in Chiba Prefecture, Japan. A virus was isolated by inoculation of fetal bovine lung cell cultures from a vesicle on a teat of an infected cow. The virus was subsequently passaged in fetal bovine lung and muscle cells in which it produced complete cytopathic changes. The virus was identified by physicochemical examinations and electromicroscopic observation as a parapoxvirus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 14 publications
2
36
1
2
Order By: Relevance
“…This is consistent with previous findings that the envelope of parapoxviruses and the plasma membrane of parapoxvirus-infected cells contain specific antigens, and that the antiserum reacts more strongly with homologous strains than with heterologous strains 9 . We found three of the 14 farms in our survey to be serologically parapoxvirus-free, as had been reported by Sentsui et al 12 , and we found the positive reaction rate in Ishikawa Prefecture to be lower than in other prefectures 5,12 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous findings that the envelope of parapoxviruses and the plasma membrane of parapoxvirus-infected cells contain specific antigens, and that the antiserum reacts more strongly with homologous strains than with heterologous strains 9 . We found three of the 14 farms in our survey to be serologically parapoxvirus-free, as had been reported by Sentsui et al 12 , and we found the positive reaction rate in Ishikawa Prefecture to be lower than in other prefectures 5,12 .…”
Section: Discussionsupporting
confidence: 89%
“…The BPSV Ishikawa-B strain was isolated from vesicles on the teats of a dairy cow in Ishikawa Prefecture in 1995 5 , and the ORFV IJS087 strain was isolated from papules on the lips of a Japanese serow in Ishikawa Prefecture in 2008 4 . After showing cytopathic effects (CPE), the cells were cocultured with Madin-Darby bovine kidney cells.…”
Section: Agid Testmentioning
confidence: 99%
“…Generally, although the mortality of parapoxvirus infection is less than 1%, the morbidity in a single herd tends to be high as in this case. In Hokkaido, Japan, Kuroda et al reported that the seroprevalence of parapoxvirus infection in sheep was 46/52 (88.5%) 9 . Parapoxviruses are closely related antigenically to each other; however, reinfection after recovery seems possible.…”
Section: Discussionmentioning
confidence: 99%
“…BPSV Chiba strain 9 was purified from the supernatant of infected cells as described previously 4 . New Zealand white rabbits were immunized hypodermically with the virus suspension in Gerbu Adjuvant LQ (Gerbu Biotechnik, Gaiberg, Germany) according to the manufacturer's instructions.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…BPSV infection usually leads to mild and transient inflammatory lesions on the muzzles of calves, except for lesion manifestations on the udders of lactating cows (Inoshima et al, 2001;Kuroda et al, 1999;Mayr & Büttner, 1990). Due to genetic heterogeneity, molecular classification of PPV remains problematic and still relies on the source of the virus isolate (Büttner & Rziha, 2002;Gilray et al, 1998;Rafii & Burger, 1985;Robinson et al, 1982Robinson et al, , 1987.…”
mentioning
confidence: 99%